Seasonally Dependent Daytime and Nighttime Formation of Oxalic Acid Vapor and Particulate Oxalate in Tropical Coastal and Marine Atmospheres - Le Yan; Yating Gao; Dihui Chen; Lei Sun; Yang Gao; Huiwang Gao; Xiaohong Yao (Atmosphere)
Oxalic acid is the most abundant low-molecular-weight dicarboxylic acid in the atmosphere, and it plays a crucial role in the formation of new particles and cloud condensation nuclei. However, most observational studies have focused on particulate oxalate, leaving a significant knowledge gap on oxalic acid vapor. This study investigated the concentrations and formation of oxalic acid vapor and oxalate in PM2.5 at a rural tropical coastal island site in south China across different seasons, based on semi-continuous measurements using an Ambient Ion Monitor-Ion Chromatograph (AIM-IC) system. We replaced the default 25 μL sampling loop on the AIM-IC with a 250 μL loop, improving the ability to distinguish the signal of oxalic acid vapor from noise. The data revealed clear seasonal patterns in the dependent daytime and nighttime formation of oxalic acid vapor, benefiting from high signal-to-noise ratios. Specifically, concentrations were 0.059 ± 0.15 μg m−3 in February and April 2023, exhibiting consistent diurnal variations similar to those of O3, likely driven by photochemical reactions. These values decreased to 0.021 ± 0.07 μg m−3 in November and December 2023, with higher nighttime concentrations likely related to dark chemistry processes, amplified by accumulation due to low mixing layer height. The concentrations of oxalate in PM2.5 were comparable to those of oxalic acid vapor, but exhibited (3–7)-day variations, superimposed on diurnal fluctuations to varying degrees. Additionally, thermodynamic equilibrium calculations were performed on the coastal data, and independent size distributions of particulate oxalate in the upwind marine atmosphere were analyzed to support the findings.